Constraints and Opportunities in Vegetables Value Chain in peri: urban Areas of Ethiopia - Almaz Giziew (Journal of Agricultural Extension Management, 2014)
Vegetable production and marketing is one of the major sources of livelihood for a large number of producers, transporters, middlemen and traders. Hence, understanding the major constraints and opportunities for production and marketing is important to improve vegetable production and marketing. To this end, the aim of this study was to identify major constraints, opportunities of production and marketing of vegetables. Multi stage sampling procedure was followed to select sample households for the study. A number of respondents at all stages of the value chain were interviewed. A total of 75 producer respondents (57 males and 18 females) drawn from Akaki-Kality sub-city, 25 retailers and one broker, two assemblers, two transporters and 15 wholesalers were interviewed using structured and semi-structured questionnaires. This study identified production constraints such as low production and productivity, flood, frost, insects and pests, limited extension support for production, quality of water, poor product handling which were among the major problems. This study also identified marketing constraints namely, imperfect pricing system, absence of law enforcement on standards, inability to have fixed market place, limited marketing extension support, lack of storage, lack of coordination among producers, lack of improvement for other actors in the channel and poor vertical linkages of producers with other value chain actors. The current government structure needs to be strengthened and channels created that directly link producers with vegetable shops, supermarkets, retailers and wholesalers in well structured institutional arrangements.